2009
DOI: 10.1073/pnas.0902020106
|View full text |Cite
|
Sign up to set email alerts
|

Protein-free small nuclear RNAs catalyze a two-step splicing reaction

Abstract: Pre-mRNA splicing is a crucial step in eukaryotic gene expression and is carried out by a highly complex ribonucleoprotein assembly, the spliceosome. Many fundamental aspects of spliceosomal function, including the identity of catalytic domains, remain unknown. We show that a base-paired complex of U6 and U2 small nuclear RNAs, in the absence of the Ϸ200 other spliceosomal components, performs a two-step reaction with two short RNA oligonucleotides as substrates that results in the formation of a linear RNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…The same can be said of the spliceosome (Will and Lührmann 2010). Although a detectable level of catalysis of an isolated step of RNA splicing can be achieved with pure snRNAs (Valadkhan et al 2009), the efficient and regulated splicing of an entire genome's collection of primary transcripts requires the collaboration of almost 200 proteins and five snRNAs in the modern spliceosome. Telomerase represents another paradigm, as it includes a canonical protein enzyme (TERT) that operates in intimate collaboration with RNA (Blackburn and Collins 2010)-so it appears to derive from more recent evolution, after protein enzymes and DNA chromosomes were well established.…”
Section: The Contemporary Rna Worldmentioning
confidence: 99%
“…The same can be said of the spliceosome (Will and Lührmann 2010). Although a detectable level of catalysis of an isolated step of RNA splicing can be achieved with pure snRNAs (Valadkhan et al 2009), the efficient and regulated splicing of an entire genome's collection of primary transcripts requires the collaboration of almost 200 proteins and five snRNAs in the modern spliceosome. Telomerase represents another paradigm, as it includes a canonical protein enzyme (TERT) that operates in intimate collaboration with RNA (Blackburn and Collins 2010)-so it appears to derive from more recent evolution, after protein enzymes and DNA chromosomes were well established.…”
Section: The Contemporary Rna Worldmentioning
confidence: 99%
“…1B) that led to the formation of a linear RNA product ( Fig. 1B; Valadkhan et al 2009). In the first step of this reaction, an internal phosphodiester bond in the Exon1 substrate is cleaved in a U6/U2-catalyzed hydrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of using engineered, protein-free RNA systems to study splicing has been recently argued (5,6). In a recent issue of PNAS, Valadkhan et al (7) demonstrated that an RNA complex derived from the spliceosome can perform a reaction that resembles splicing (Fig. 1B).…”
mentioning
confidence: 99%